AN EVALUATION OF REACTIVE FLUID FLOW AND TRACE ELEMENT MOBILITY IN SUBDUCTING SLABS - Zack T.; John T. (My University, 2007)
Permeabilities in the subducting slab appear to be too low and dihedral angles between fluid and relevant minerals too high to allow for porous flow, hence fluid channelization is critical for the understanding of subduction zone fluid fluxes. In this review we will outline how fluid channelization controls reaction rates and element redistributions during metamorphism of the subducting plate as well as trace element compositions of subduction-related fluids during flow.Channelized fluid flow predicts that from a rock point of view, most formerly subducted material will show only very limited evidence for fluid flow, consistent with the rarity of observed high fluid fluxes in subduction-related rocks. Aqueous fluid produced by dehydration reactions will not percolate through large rock volumes, but rather will be carried away from the dehydration sites by a veining network. Indeed evidence for significant aqueous-fluid fluxes have been found in high-pressure veins with adjacent selvages. In such selvages, large lithophile elements (LILE's) generally show the highest mobilities, followed by light (L) rare earth elements (REE) and then heavy (H) REE. Compared to high field strength elements (HFSE), even Th shows higher mobilities.From a fluid point of view, equilibrium between aqueous fluid and surrounding rock will only be approached at sites of fluid production and mineral reaction. However, this fluid can be significantly modified while moving upwards through a veining network where the wallrocks are out of equilibrium with the fluid. In a subducting slab, such reactive fluid flow can preferentially dissolve minerals and release their trace elements (e.g. Ba in phengite, Th and La in monazite). The degree of change in aqueous-fluid composition will depend on the amount of fluid–mineral surface interaction. The chemical exchange reactions will not be possible to model by trace element partition coefficients alone, instead future models need to incorporate kinetic parameters such as surface reaction rates.
Keywords: BLUESCHISTS; ECLOGITES; REACTIVE FLUID FLOW; SUBDUCTION ZONES; TRACE ELEMENTS